Implementasi Kebijakan Merdeka Belajar Kampus Merdeka Melalui Program Magang dan Studi Independen Bersertifikat (MSIB) di Fakultas Pertanian UPN “Veteran” Jawa Timur - Effendy, Amelia Diva; Hertati, Diana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Around 12% of unemployment in Indonesia is dominated by Diploma and Bachelor graduates. This is because there is no link and match. Therefore, in 2020 the Ministry of Education and Culture released the Independent Campus Learning (MBKM) policy. The aim of this research is to determine the implementation of the MBKM Policy through the MSIB Program in Certified Internship Activities at the Faculty of Agriculture, UPN "Veteran" East Java. The theory used is the implementation of policies by Edward III, namely communication, resources, disposition and bureaucratic structure. This research uses qualitative methods with descriptive research type. Data collection was carried out by means of interviews, observation and documentation. The research results show that first, the communication focus still needs to increase clarity and consistency in the coordination process of policy implementers so that it has not been implemented well. Second, the focus on resources still requires an increase in the number of PT Coordinator staff so that it has not been implemented well as a whole. Third, the focus of disposition, namely cognition, implementing responses, and response intensity can be said to have been implemented well as a whole. Fourth, the focus of the bureaucratic structure is that there are implementation SOPs that have not been implemented so they have not been implemented properly. Therefore, it can be concluded that the implementation of the MBKM policy of the MSIB program in Certified Internship activities at the Faculty of Agriculture, UPN "Veteran" East Java has not been implemented well.